Effects of supplementary mats on ground reaction forces and neuromuscular pre-activation in gymnastics landings - Schwameder, H.; Schaufler, D.; Strutzenberger, G.; Alexander, N. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to analyse the effects of supplementary mats on ground reaction forces (GRF) and neuromuscular activation of selected leg muscles during gymnastics landings. Participants (n=10) performed landings from 1 m and 2 m height onto a landing mat and landing mat plus a soft supplementary mat. EMG of lower extremity muscles and ground reaction forces were measured. Results showed a decrease between 15% and 40% of the peak GRF and the peak rate of force development (RFD), respectively, when using supplementary mats. While the duration of pre-activation remained unchanged, the amount of pre-activation was reduced when landing on supplementary mats. From a biomechanical point of view supplementary mats can be recommended in gymnastics landings.